Five Years Facts of Bladder Cancer at West Java’s Top Referral Hospital, in Indonesia - Vivien Kate Perix; Sri Suryanti; Aaron Tigor Sihombing (Faculty of Medicine Universitas Padjadjaran, 2017)
Background: Bladder cancer is the second most common genitourinary cancer and its incidence is rising 15% annually in Indonesia. Smoking is the leading risk factor of bladder cancer and two thirds of men in Indonesia smokes. This study was conducted to describe the characteristics of bladder cancer based on sex, age and histopathology type in West Java’s Top Referral Hospital, Indonesia. Methods: This study was a descriptive study conducted during theperiod of September to November 2015 using 372 histopathological medical records of patients who had primary and secondary bladder cancer at the Pathology Department, Dr. Hasan Sadikin General Hospital Bandung from January 2010 to December 2014. Data were collected using total sampling method based on the characteristics of age, sex histopathology type, and staging of bladder cancer.Results: Out of the 372 cases, 298 cases were male and 38 cases were female with a male to female ratio of 7.8:1. The age group with the highest incidence was the 50–59 years old group. Infiltrating urothelial carcinoma was the most common histopathology type (71.1%) in primary cancers, 66.1% of cases was muscle invasive while 33.9% was non muscle invasive. Staging pT1 had the most number of cases. The most common site of origin for secondary neoplasm was cervix with adenocarcinoma as the most common histopathology type. Conclusions: Bladder cancer is more common in male than female and peaks at the sixth decade of life. Infiltrating urothelial carcinoma is the most common histopathology type. [AMJ.2017;4(1):94–9] DOI: 10.15850/amj.v4n1.1028